Individual Assignment: Business Plan Report Fundamentals of Entrepreneurship (ENT300) : Go-gurt Enterprise / Deena Ashikin Yahaya - Yahaya, Deena Ashikin (2020)
Basically, this business is based on a new sole proprietorship where the businesses it owned by just one individual. Owner of sole proprietorship will experience unlimited liability, have less paperwork and fewer additional legal formalities that will easing registration process. I am the owner of the business that personally responsible for its debt. The business capital is amounted RM 80,000. Go-gurt Enterprise is a business that focusing on customers’ needs and it is to help them have provide healthy lifestyle, fresh and non-sugar drink to valuable customers and to be world’s No.1 yogurt and smoothie brand. I am offering customers Go-gurt which is profit retail business motivated to make every good yogurt in helping customer improve their healthy lifestyle. To those likes to drink carbonate, they should try my Go-gurt product which have a lot of benefit. Go-gurt we were using fresh or original fruits without adding any sugar. Because we want customer to feel the originality fruits itself. There are variety flavor of fruits that customer can choose. Go-gurt were incorporated at Bayan Lepas, Pulau Pinang. Price of the Go-gurt in size medium is RM13.50. Nowadays, we keep on listening a lot of people suffered from diabetes cause of drinks something that have a lot of sugar it happened especially to adult. In some research, there is approve which show that Malaysia having high number of diabetes patient. It is happened because intake of sugar.so, with trying my Go-gurt may not increase number of sugars in them. Because Go-gurt were using fresh or original fruits without adding any sugar plus yogurt also customer can feel the originality fruits itself. I expected that my business will become more developed in the near future because with this new branding name which is Go-gurt, the demand will increase not only during promotion day but in daily basis. This will give more advantages for me to make my product and improving it to more profitable and capable in long run. Everybody should live in healthy lifestyle which they need to eat lots of food that have vitamin. That where good to body.